Increased Postnatal Cardiac Hyperplasia Precedes Cardiomyocyte Hypertrophy in a Model of Hypertrophic Cardiomyopathy - Farrell, Emily T.; Grimes, Adrian C.; de Lange, Willem J.; Armstrong, Annie E.; Ralphe, J. Carter (Frontiers in Physiology, 2017)
Rationale –Hypertrophic cardiomyopathy (HCM) occurs in 0.5% of the population and is a leading cause of sudden cardiac death in young adults. Cardiomyocyte hypertrophy has been the accepted mechanism for cardiac enlargement in HCM, but the early signaling responsible for initiating hypertrophy is poorly understood. Mutations in cardiac myosin binding protein C (MYBPC3) are among the most common HCM-causing mutations. Ablation of Mybpc3 in an HCM mouse model (cMyBP-C-/-) rapidly leads to cardiomegaly by postnatal day (PND) 9, though hearts are indistinguishable from wild-type (WT) at birth. This model provides a unique opportunity to explore early processes involved in the dramatic postnatal transition to hypertrophy. Methods and Results – We performed microarray analysis, echocardiography, qPCR, immunohistochemistry (IHC), and isolated cardiomyocyte measurements to characterize the perinatal cMyBP C / phenotype before and after overt hypertrophy. cMyBP-C-/- hearts showed elevated cell cycling at PND1 that transitioned to hypertrophy by PND9. An expanded time course revealed that increased cardiomyocyte cycling was associated with elevated heart weight to body weight ratios prior to cellular hypertrophy, suggesting that cell cycling resulted in cardiomyocyte proliferation. Animals heterozygous for the cMyBP-C deletion trended in the direction of the homozygous null, yet did not show increased heart size by PND9. Conclusions – Results indicate that altered regulation of the cell cycling pathway and elevated proliferation precedes hypertrophy in the cMyBP-C-/- HCM model, and suggests that increased cardiomyocyte number contributes to increased heart size in cMyBP-C-/- mice. This pre-hypertrophic period may reflect a unique time during which the commitment to HCM is determined and disease severity is influenced.